SURVEY TINGKAT KESEGARAN JASMANI SISWA SMAN 9 KAB. BONE - Andi Khemal Akbar (Didaktika : Jurnal Kependidikan, 2019)
This study aims to determine the level of physical fitness of students of SMAN 9 Bone District. The method used in this research is a descriptive quantitative method with a survey approach. The population in this study was 418 students of SMAN 9 of Bone Regency including 266 female and 152 male students. Meanwhile, this study applied a random sampling technique. Then the sample was taken using random sampling technique involving 40 male and 40 female students. Data was collected by using the Indonesian Physical Fitness Test (TKJI) measurement and test instrument for ages 16-19 years old. All the test items were carried out at one time. The result shows that among 40 male students, there were six students or 15% who were in the excellent category, 16 students or 40% on the good category, eight students or 20% on the fair category, six students or 15% on the poor category, and the rest four students or 10% of the total sample studied on the very poor category. Whereas for the female students, among 40 female students, there were four students or 10% on the excellent category, 16 students or 40% on the good category, there were; four students or 10 % on the fair category, 12 students or 30% on the poor category, and four students or 10% of the total sample studied on the very poor category.